Restorative Justice in the Perspective of Modern Criminal Law: Challenges and Regulatory Reforms in Indonesia (Lembaga Pengembangan Kinerja Dosen, 2026)
Restorative Justice in the Perspective of Modern Criminal Law: Challenges and Regulatory Reforms in Indonesia by a retributive approach that emphasizes punishing the offender as a form of retribution. However, this approach is considered unable to provide comprehensive justice, especially for the victims, and is not effective in resolving the social conflicts caused by criminal acts. Therefore, the concept of restorative justice has emerged as a new paradigm that emphasizes the restoration of victim losses, the responsibility of the perpetrator, and community involvement in the resolution of cases. This research aims to analyze the concept and theoretical foundations of restorative justice, its implementation in the criminal justice system in Indonesia, as well as the challenges and the need for regulatory renewal. The research method used is normative legal research with a legislative and conceptual approach, supported by secondary data as the main source. The research results show that restorative justice has been regulated in various sectoral regulations, such as Police Regulation Number 8 of 2021, Attorney General Regulation Number 15 of 2020, Law Number 11 of 2012, and Supreme Court Regulation Number 1 of 2024. However, the regulations are still partial and not integrated into a comprehensive legal framework, leading to differences in understanding and application among law enforcement officials. Therefore, the establishment of a specific law on restorative justice is necessary to ensure legal certainty, uniform application, and to create a more humane, just, and recovery-oriented criminal justice system.